Organizational Change Management in Educational Institutions as a Learning Organization - Özan, Mukadder Boydak; Yaraş, Zübeyde; Yıldırım, Fatih Mehmet (My University, 2021)
Purpose: In the research, it is aimed to determine the importance of change management for educational institutions and toreveal the importance of change management in schools as a learning organization within the framework of changemanagement, and the driving and limiting forces in the change process. Design/Methodology/Approach: The research was structured in the \"phenomenology\" pattern within the framework of basicqualitative research. The sample group of the study was formed by using the \"Simple Random Method\", which is one of the\"Probability-Based Sampling\" methods. In the 2017-2018 academic year, 30 teachers working in schools in the central districtof Elazığ took part in the study group. A semi-structured interview form consisting of three open-ended questions was used asa data collection tool. The data were analyzed using the “thematic analysis” method. Findings: When the results obtained are evaluated, it is seen that change management is important in terms of organizationalsustainability and organizational progress. In addition, it is mostly stated that the integration of technology and informationtechnologies into education is the driving force of change; On the other hand, it has been concluded that the reasons such aslack of information, lack of trust in the administrator, and lack of communication in the change process limit the change. Highlights: Schools, which are educational institutions, have a dynamic environment when evaluated from a broad perspective.One of the indicators of this dynamism is that it is a learning organization depending on its learning capacity. The ability tomanage changes has been considered important in the development and transformation of schools, which are learningorganizations, together with all the resources they have.
Keywords: Eğitim; Eğitim Araştırmaları